'Getting the Balance between Encouragement and Taking Over' — Reflections on Using a New Stroke Self‐Management Programme. (5th July 2012) - Jones, Fiona; Livingstone, Elizabeth; Hawkes, Louise
Abstract: Background and Purpose: This paper presents findings from a study which aimed to explore contextual, personal and professional factors in applying training in the use of a new stroke self‐management programme. Methods: Practitioners completed in‐depth case reflections as part of their two‐day training in the Bridges stroke self‐management programme (SSMP). The study utilized a qualitative approach to explore the understanding and meaning participants gave to their experiences of using the SSMP. Data from case reflections were analysed using a thematic content analysis. Results: Data from 60 case reflections were included in the analysis. Several themes were prominent including: timing, belief in the concept of self‐management, congruence with goal setting, balance of power and subtleties and sensitivities of using the SSMP. The use of in‐depth case reflections enabled a personal awareness of the complexities of supporting self‐management after stroke. Participants reflected on their communication styles and interactions and how they influence the development of self‐management skills in individuals post‐stroke. Conclusion: Case reflections offered an opportunity for participants who had received training in the use of an SSMP to explore their experiences of using the programme with individuals post‐stroke. This enabled personal reflection on learning and facilitated a wider discussion on the professional and organizational context concerning integration of a self‐management programme into stroke rehabilitation. The paradox between professionals having a role as 'experts' and the subtle changes in practice towards a more collaborative therapeutic relationship to support self‐management needs further exploration. Implication for practice: Physiotherapists were required to make a change in their practice from traditional, educational, hands on approaches to one which gave more prominence to facilitating an individual's problem solving, collaborative goal setting and decision‐making post‐stroke. This study highlights a number of issues relevant to professional learning and education in respect of self‐management. Copyright © 2012 John Wiley & Sons, Ltd.